A radioimmunoassay for hepatitis A antigen and antibody. Issue 7 (July 1979) - Skidmore, S J; Boxall, E H
Abstract : The HAVAB radioimmunoassay for the detection of antibody to hepatitis A is assessed. Its modification to detect virus in faecal samples is described and in this it was found to be more sensitive and specific than electron microscopy.